And then there were many: insights from the tangled taxonomy of the Antarctic brittle star Ophioplinthus gelida (Echinodermata: Ophiuroidea) - Chester J. Sands; Timothy D. O’Hara; Alice Guzzi; William P. Goodall-Copestake; Peter Convey; Bhavani E. Narayanaswamy; Rafael Martín-Ledo; Sabine Stöhr (Frontiers in Marine Science, 2025)
To effectively manage biological assemblages, a sound knowledge of the biodiversity is essential. The Southern Ocean shelf benthic assemblages are typically comprised of species, the names of which are shared across the huge expanse of the region, indicating large population sizes and good connectivity, inferring resilience. This is despite two decades of studies identifying cryptic or unrecognised species in many benthic groups. In this study we examine the common and widespread species Ophioplinthus gelida (Koehler, 1900) and Ophioplinthus martensi (Studer, 1885), both regarded as occurring throughout the Southern Ocean on continental and island shelves. The two species show subtle differences in morphology, despite O. gelida having very plastic character states. Genetic analysis using mitochondrial sequences shows that the two species are part of a radiating clade with ten distinct elements, six of which group as O. gelida and four as O. martensi . Further investigation showed that one of these elements can be attributed to Ophioplinthus carinata (Studer, 1876), not previously identified on the Antarctic shelf, but shown here to be a dominant fraction of the O. “gelida” in our collections. Furthermore, O. “martensi” from its type locality of South Georgia is genetically similar to Ophioplinthus intorta (Lyman, 1878), from Marion Island, but distinct from those collected from the Antarctic shelf, which may then be considered Ophioplinthus inermis (Bell, 1902). A fifth clade of O. martensi collected from waters deeper than 2000 m was not part of this radiation but grouped together with more distantly related Ophioplinthus species. In general, the genus displays a wide range of morphological character states, varying greatly within O. gelida elements, and often shared between species. Several taxa outside of the O. gelida complex may also include unrecognised cryptic species, making reliable field identifications challenging, and greatly increasing the recognised species diversity and regional endemism.

Sponges (Porifera) from the Ross Sea (Southern Ocean) with taxonomic and molecular re-description of two uncommon species - Gabriele Costa; Angelina Lo Giudice; Maria Papale; Carmen Rizzo; Maurizio Azzaro; Alice Guzzi; Marco Grillo; Marco Bertolino (Polar Biology, 2023)

Quantification of blue carbon pathways contributing to negative feedback on climate change following glacier retreat in West Antarctic fjords - Nadescha Zwerschke; Chester J. Sands; Alejandro Roman‐Gonzalez; David K. A. Barnes; Alice Guzzi; Stuart Jenkins; Carlos Muñoz‐Ramírez; James Scourse (Global Change Biology, 2022)
Global warming is causing significant losses of marine ice around the polar regions. In Antarctica, the retreat of tidewater glaciers is opening up novel, low‐energy habitats (fjords) that have the potential to provide a negative feedback loop to climate change. These fjords are being colonized by organisms on and within the sediment and act as a sink for particulate matter. So far, blue carbon potential in Antarctic habitats has mainly been estimated using epifaunal megazoobenthos (although some studies have also considered macrozoobenthos). We investigated two further pathways of carbon storage and potential sequestration by measuring the concentration of carbon of infaunal macrozoobenthos and total organic carbon (TOC) deposited in the sediment. We took samples along a temporal gradient since time of last glacier ice cover (1–1000 years) at three fjords along the West Antarctic Peninsula. We tested the hypothesis that seabed carbon standing stock would be mainly driven by time since last glacier covered. However, results showed this to be much more complex. Infauna were highly variable over this temporal gradient and showed similar total mass of carbon standing stock per m 2 as literature estimates of Antarctic epifauna. TOC mass in the sediment, however, was an order of magnitude greater than stocks of infaunal and epifaunal carbon and increased with time since last ice cover. Thus, blue carbon stocks and recent gains around Antarctica are likely much higher than previously estimated as is their negative feedback on climate change.

Towards a robust baseline for long-term monitoring of Antarctic coastal benthos - Paola Piazza; Stefano Antonio Gattone; Alice Guzzi; Stefano Schiaparelli (Hydrobiologia, 2020)

Underwater photogrammetry in Antarctica: long-term observations in benthic ecosystems and legacy data rescue - Paola Piazza; Vonda Cummings; Alice Guzzi; Ian Hawes; Andrew Lohrer; Simone Marini; Peter Marriott; Fabio Menna; Erica Nocerino; Andrea Peirano; Sanghee Kim; Stefano Schiaparelli (Polar Biology, 2019)